Taxonomic studies on seven species of the genus Opopaea (Araneae, Oonopidae) from Kenya - Yanfeng Tong; Shijia Liu; Esther N. Kioko; Grace M. Kioko; Shuqiang Li (African Invertebrates, 2019)
Seven species of the genus Opopaea Simon, 1892 from Kenya are recognized, including five new species: O. berlandi (Simon & Fage, 1922), O. kulczynskii (Berland, 1914), O. makadara Tong & Li, sp. nov. (♀♂), O. ngangao Tong & Li, sp. nov. (♀♂), O. ngulia Tong & Li, sp. nov. (♂), O. sheldrick Tong & Li, sp. nov. (♀♂), and O. wundanyi Tong & Li, sp. nov. (♀♂). Morphological descriptions and illustrations of all the species are given. All types are preserved in the National Museums of Kenya in Nairobi, Kenya (NMK).